2002
DOI: 10.4049/jimmunol.168.1.332
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Protection Against Functional CTL Abnormalities in Simian Human Immunodeficiency Virus-Infected Rhesus Monkeys

Abstract: Accumulating evidence suggests that HIV-specific CD8+ CTL are dysfunctional in HIV-infected individuals with progressive clinical disease. In the present studies, cytokine production by virus-specific CTL was assessed in the rhesus monkey model for AIDS to determine its contribution to the functional impairment of CTL. CTL from monkeys infected with nonpathogenic isolates of simian and simian-human immunodeficiency virus expressed high levels of IFN-γ, TNF-α, and IL-2 after in vitro exposure to a nonspecific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…It has been recently reported that dysfunction of IL-2 and TNF-␣ production might be observed even earlier than the loss of IFN-␥ production by HIV-specific CD8 ϩ CTL (66). It was demonstrated that i.m.…”
Section: Discussionmentioning
confidence: 97%
“…It has been recently reported that dysfunction of IL-2 and TNF-␣ production might be observed even earlier than the loss of IFN-␥ production by HIV-specific CD8 ϩ CTL (66). It was demonstrated that i.m.…”
Section: Discussionmentioning
confidence: 97%
“…17 As in human infection with HIV, functional defects in SIV-specific CD8 ϩ T cells have been reported, potentially explaining why virtually all SIV-infected rhesus macaques progress to simian AIDS and death despite a readily measurable CD8 ϩ T-cell response. [17][18][19][20] Therefore, understanding factors that regulate the function(s) of SIV-and HIV-specific CD8 ϩ T cells is critical in the fight against AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…17 As in human infection with HIV, functional defects in SIV-specific CD8 ϩ T cells have been reported, potentially explaining why virtually all SIV-infected rhesus macaques progress to simian AIDS and death despite a readily measurable CD8 ϩ T-cell response. [17][18][19][20] Therefore, understanding factors that regulate the function(s) of SIV-and HIV-specific CD8 ϩ T cells is critical in the fight against AIDS.Chronic viral infection with ongoing antigenic stimulation often results in exhaustion of virus-specific CD8 ϩ T cells. 21,22 Chronically stimulated virus-specific CD8 ϩ T cells express only low levels of receptors for IL-7 and IL-15 23 and lose the ability to maintain homeostatic proliferation.…”
mentioning
confidence: 99%
“…HIV-specific CTL responses can recognize and kill HIV infected cells and are effective in controlling HIV-1 replication during the course of natural infection [7][8][9]. Vaccines which elicit these types of responses can also control the replication of pathogenic retroviruses and protect against the development of immunodeficiency and death in nonhuman primate (NHP) models [10][11][12][13][14][15][16][17][18][19]. The current mechanisms for induction of potent CTL mediated immunity include immunogen delivery by attenuated viral vectors, bacterial vectors, direct plasmid DNA injection, and co-delivery of vaccine adjuvants (reviewed in [20][21][22]).…”
Section: Introductionmentioning
confidence: 99%